Experience of postnatal mothers with the baby massage program - Chan, K.G; Saloma, Pawi; Lee,, Shalin Wan Fei; Hii, Emily; Helmy, Hazmi; Ooi, Chor Yau; Zurraini, Arabi (2017)
The International Association of Infant Massage has developed an infant massage program that promote nurturing touch and advocates that children and parents are to be respected and valued. Studies have shown that the practice of infant massage provide benefits both for mothers and babies. One of the aims of the study is to explore postnatal mothers' experience with infant massage program using focus group discussion. Study has been conducted at selected maternal and child health clinics around Kuching, Sarawak. As part of an ongoing comparative cohort study, it involves recruitment of postnatal mothers who are from the clinics. They were taught the adapted infant massage program by a certified infant massage instructor over 4 sessions at weekly interval. They were asked to do massage for their babies at home twice a day over 15 minutes each time. Focus group interviews revealed that their babies slept better, more relaxed, while the mothers enjoyed bonding time with their babies. The group massage sessions in the clinic were perceived as a time to meet other mothers for friendship and to share experience on child care. Preliminary findings provide evidence which may influence maternal and child care provision in Malaysia.